2018
DOI: 10.1051/0004-6361/201732185
|View full text |Cite
|
Sign up to set email alerts
|

Validity of abundances derived from spaxel spectra of the MaNGA survey

Abstract: We measured the emission lines in the spaxel spectra of MaNGA (Mapping Nearby Galaxies at Apache Point Observatory) galaxies in order to determine the abundance distributions therein. It has been suggested that the strength of the low-ionization lines, R2, N2, and S2, may be increased (relative to Balmer lines) in (some) spaxel spectra of the MaNGA survey due to a contribution of the radiation of the diffuse ionized gas. Consequently, the abundances derived from the spaxel spectra through strong-line methods m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…We found in a previous study (Pilyugin et al 2018) that the three-dimensional R calibration, which uses the N 2 , R 2 and R 3 lines, produces reliable abundances for regions (spaxels) with H II region-like spectra in the MaNGA galaxies. One should distinguish clearly two questions: the nature of the line-emitting gas (the sources of the ionizing radiation) and the diagnostic of the emitting gas (the abundance determination).…”
Section: Abundance and Abundance Gradientmentioning
confidence: 83%
See 1 more Smart Citation
“…We found in a previous study (Pilyugin et al 2018) that the three-dimensional R calibration, which uses the N 2 , R 2 and R 3 lines, produces reliable abundances for regions (spaxels) with H II region-like spectra in the MaNGA galaxies. One should distinguish clearly two questions: the nature of the line-emitting gas (the sources of the ionizing radiation) and the diagnostic of the emitting gas (the abundance determination).…”
Section: Abundance and Abundance Gradientmentioning
confidence: 83%
“…Therefore, we obtained the position angle of the major axis of the galaxy, the galaxy's inclination angle, and the rotation velocity from the analysis of the Hα velocity field. The normalized histogram of the differences V Hβ -V Hα between the line-of-sight velocities measured for Hβ and Hα emission lines in 46,350 regions (spaxels) in MaNGA galaxies (Pilyugin et al 2018).…”
Section: Approachmentioning
confidence: 99%
“…It has been found that the three-dimensional R calibration from produces reliable abundances for MaNGA galaxies, that is, the R-calibration produces abundances compatible to the T e -based abundance scale and is workable over the whole metallicity scale of H II regions (Pilyugin et al 2018(Pilyugin et al , 2019Zinchenko et al 2019a,b). We use those relations for abundance determinations also here.…”
Section: Mapping the Properties Of Our Galaxiesmentioning
confidence: 99%
“…We examine the images of galaxies as represented by their surface brightness distribution maps in Fig. 1 The surface brightness distribution within a galaxy is fitted by a broken exponential profile for the disc and by a general Sérsic profile for the bulge following to our previous paper (Pilyugin et al 2018). We use the surface-brightness profile in solar units for the bulge-disc decomposition.…”
Section: Morphological Signs Of An Interaction or Mergermentioning
confidence: 99%
“…Panel a1 of Fig. 2 shows the surface brightness distribution in the B band across the image of UGC 4056 in sky coordinates (pixels).The geometric parameters of UGC 4056 (the coordinates of the centre X 0 = 38.5 pixels and Y 0 = 37.5 pixels, the inclination angle i = 64.2 • , and the position angle of the major axis P A = 208.4 • ) were obtained in our current study from the analysis of the surface brightness map in the way described in Pilyugin et al (2018). The formal error is 0.5 pixels for X 0 , Y 0 and 1 • for the inclination and PA.…”
Section: General Properties Of Ugc 4056mentioning
confidence: 99%